2021
DOI: 10.1186/s13613-021-00891-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term quality of life in necrotizing soft-tissue infection survivors: a monocentric prospective cohort study

Abstract: Background Compared to other life-threatening infection survivors, long-term health-related quality of life (QOL) of patients surviving necrotizing soft-tissue infections (NSTI) and its determinants are little known. In this monocentric prospective cohort including NSTI survivors admitted between 2014 and 2017, QOL was assessed during a phone interview using the 36-Item Short-Form Health Survey (SF-36), the Hospital Anxiety and Depression (HAD), the activity of daily living (ADL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…After the acute phase, 32.3% of patients required a remote skin graft, after a median time of 28 days (13–39) after the first surgical debridement, with no significant difference within both predefined subgroups. Consistent with previous series [ 8 ], 15.7% of patients underwent amputation.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…After the acute phase, 32.3% of patients required a remote skin graft, after a median time of 28 days (13–39) after the first surgical debridement, with no significant difference within both predefined subgroups. Consistent with previous series [ 8 ], 15.7% of patients underwent amputation.…”
Section: Resultssupporting
confidence: 91%
“…Hospital mortality ranges from 9.3 to 29.3%, with disabling sequelae for 30% of survivors [ 1 , 6 , 7 ]. Morbidity among survivors includes potential amputations and profound impact on long-term health-related quality of life [ 3 , 8 , 9 ]. Initial misdiagnosis is frequent [ 10 ], leading to a delayed surgical debridement of infected tissues, one of the main modifiable prognostic factors [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the year following ICU discharge, survivors displayed a severe reduction in force development and endurance contraction [ 8 ], reported by patients as impacting physical performance and health-related QOL [ 9 ]. These consequences persist at 5 years with a persistent limitation in the 6-min walk test [ 10 12 ], an impairment in aerobic capacities (decrease in VO2 max) frequently involved in muscle limitations [ 13 ], and still have an impact on physical performance and health-related QOL [ 10 12 ]. This has been mainly studied after septic shock [ 9 ] and ARDS [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Czymek et al research about QoL after Fournier’s gangrene showed similar results as Suijker et al, lowered levels of HRQoL in the physical domains [ 15 ]. Urbina et al found that patients suffering from necrotizing skin and soft-tissue infections (NSTI) had lower levels of HRQoL in multiple subdomains when compared to non-NSTI septic shock patients and when compared to NSTI patients which were not admitted to the ICU during hospitalization [ 16 ]. When compared to the research about burns these research are all much smaller (number of cases range from 10 to 30) and no systematic review has been performed yet.…”
Section: Introductionmentioning
confidence: 99%